Identification the 2013 Curriculum Teacher's Book to Determine the Character Values of Class X Students on Circular Motion Material - Astalini Astalini*; Darmaji Darmaji; Dwi Agus Kurniawan; Feliza Paramitha Sinaga; Miftahul Zannah Azzahra; Elza Triani (Jurnal Pendidikan Sains Indonesia, 2023)
The character of school students is currently in the declining category. This is due to the lack of emphasis on the time of the learning process and affects the level of success of the functions and objectives of national education. This study aims to determine the characters that are not embedded in the physics learning process for class X material for circular motion. The research method used is a qualitative method with the type of documentation research. The researcher uses a documentation study because the subject used is a 2013 curriculum teacher's book for class X circular motion. After studying the circular motion material, it is known that there are 18 characters that must be instilled during the physics learning process. However, these 18 characters are not fully embedded because there are some characters that are missing and will have a continuous negative impact on students. Due to the imperfection of this research, in the future, in the textbook of physics learning teacher class X on Circular Motion in the 2013 curriculum and its subsequent development, more attention should be paid to the character of students so that all these characters are fulfilled in order to create a good generation